SELECTION AND EVALUATION SUPPLIER BY CONTRACTOR: CASE STUDY IN INDONESIA - Andi Theo Haryanto; Paul Nugraha; I Gede Agus Widyadana (Program Studi Magister Teknik Sipil - Petra Christian University, 2019)
This research will discuss about contractors with concrete suppliers and formwork suppliers. The research is conducted to look for ranking criteria and sub-criteria used by contractors to selecting and evaluating concrete and formwork suppliers. The criteria and sub-criteria are refer to Ho et al., (2007) and three new sub-criteria are added, which are a guarantee, lowest price guarantee, and payment term. The contractor classification is divided into four namely general classification, NPK classification consisting of non-classification; individual; small business, medium business classification, and big business classification. Ranking for criteria and sub-criteria are sought based on the mean value for each classification material both in the context of selection and evaluation. After finding the ranking, it is sought whether there is a difference of importance between the NPK classification, middle, and large of the priority sub-criteria in general classification using the Kruskal Wallis test.